Impact of Plastic Waste on The Volumetric Characteristics and Resilient Modulus of Asphalt Concrete - Husham Al-Tuwayyij; Noorance Al-Mukaram; Sarah S. Musa (Civil Engineering Journal, 2023)
Recently, the use of plastic in many products has led to a huge amount of plastic waste, which is typically difficult to treat and expensive to recycle. This problem has been considered by many researchers and environmental organizations as requiring serious considerations about recycling and reusing plastic waste in different fields, such as asphalt mixtures. In this paper, aggregate passing a 4.75-mm sieve was replaced by 5, 7, 9, and 11% of plastic bottles used for drinking purposes. The dry method was adopted in this work, and the changes in the mixture’s volumetric properties were investigated using the Marshall method. A repeated indirect tensile load test was also conducted to determine the mixture’s resilient modulus. Marshall’s stability, air voids, unit weight, flow, and voids in mineral aggregates were examined. The results were compared and analyzed with the base sample. It was observed that adding plastic decreased aggregate consumption and reduced the optimum asphalt content (OAC). Additionally, the volumetric properties of the mixture improved and its service life was extended after adding plastic. It was also observed that the value of the resilient modulus (RM) increased when the percentage of added plastic increased as well. Reuse of plastic in asphalt mixtures achieves the concept of an environmentally friendly solution in the transportation area because it reduces the amount of asphalt and aggregates and reduces the costs of recycling plastic. Moreover, the optimal plastic content in this paper was achieved at 11%. Doi: 10.28991/CEJ-2023-09-04-012 Full Text: PDF